Phenotypic response to food availability in sea urchin larvae and impact of light during development and growth - Cocurullo, Maria; Kirwan, John D.; Arnone, Maria Ina (Frontiers in Ecology and Evolution, 2025)
Phenotypic plasticity, the ability of a genotype to produce different phenotypes in response to environmental conditions, plays a crucial role in adaptation and evolution and can occur during development or adulthood. Sea urchin larvae exhibit developmental plasticity by adjusting their arm length in response to food availability. In this study, we investigated the phenotypic responses of three sea urchin species: Paracentrotus lividus and Arbacia lixula from the Mediterranean Sea, and Strongylocentrotus purpuratus from the Pacific Ocean. In all species, we observed that larvae reared under a 12h light:12h dark cycle exhibited phenotypic responses to food availability. However, the response was suppressed in larvae reared under constant darkness, suggesting that light has a role in mediating this phenotypic plasticity. Moreover, larvae grown in constant darkness were generally smaller than those exposed to light, with the magnitude of this effect varying among species, indicating that light exposure influences not only plasticity but also baseline growth rates. These findings underscore the utility of sea urchins as a model for studying ecological and evolutionary processes shaping phenotypic responses and suggest that light has an important impact on development and growth in sea urchins.